2016
DOI: 10.2147/copd.s105516
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bronchitis is an independently associated factor for more symptom and high-risk groups

Abstract: BackgroundThe chronic bronchitis (CB) phenotype has been associated with poor quality of life and an increased risk of disease in patients with COPD. However, little information exists regarding the relationship between the CB phenotype and the COPD assessment test (CAT) score. The goal of this study was to reveal the different pattern of CAT scores between CB and non-CB patients. Moreover, we aimed to investigate whether the CB phenotype is an independently associated factor for more symptom and high-risk gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Fifty-seven patients had CAT scores ≥3 (20.4%). When the CAT score cut-off was <3, the percentages of alleged patients with CB were too low compared with previously reported CB percentages, 3 so only the CB group, defined as patients with COPD with a CAT score ≥3, were evaluated in depth. Table 1 shows a comparison of the clinical characteristics of the CB and non-CB groups.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Fifty-seven patients had CAT scores ≥3 (20.4%). When the CAT score cut-off was <3, the percentages of alleged patients with CB were too low compared with previously reported CB percentages, 3 so only the CB group, defined as patients with COPD with a CAT score ≥3, were evaluated in depth. Table 1 shows a comparison of the clinical characteristics of the CB and non-CB groups.…”
Section: Resultsmentioning
confidence: 96%
“… 1 Patients with CB are generally more symptomatic, with a higher COPD assessment tool (CAT) score, and have a lower quality of life, scoring higher on the total SGRQ. 2 , 3 Many studies have also shown that impaired pulmonary function is more evident for the CB type. 3 Forced expiratory volume in 1 second (FEV 1 ) and FEV 1 /forced vital capacity (FVC) are lower for the CB type.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic bronchitis patients with COPD are characterized by airway wall thickening as detected via thoracic CT. 6,14 Such patients are often more symptomatic and show more frequent exacerbations compared to patients without chronic bronchitis. [24][25][26][27] Furthermore, MWA% is also correlated with small airway disease, 10 and it may also have had a detrimental effect on COPD patients with mixed phenotype. We found that frequent exacerbations in the mixed phenotype may have led to increased mortality, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%